2019
DOI: 10.3390/su11205580
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Online Higher Education in the Face of the Sustainability Objectives of the United Nations: Carbon Footprint, Accessibility and Social Inclusion

Abstract: This article analyses three of the Sustainable Development Goals (SDGs) gathered by the 2030 Agenda and adopted by the United Nations, and how online educational models may help to reach these goals. Specifically, the three goals discussed through this article are: i) Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all (Goal 4); ii) reduce inequality within and among countries (Goal 10); and iii) take urgent action to combat climate change and its impacts (Goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Previous literature [5,[22][23][24] and some of the studies reviewed here [54,56,74,76,79,86,87,93,95] contend that it is necessary to provide additional training to improve knowledge of ASD and to overcome misconceptions and lack of information. It is important to consider this pressing need for training not only for pre-service teachers in teacher training colleges [39][40][41]96], but also lifelong learning for in-service teachers of mainstream schools, universities and other educational placements [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature [5,[22][23][24] and some of the studies reviewed here [54,56,74,76,79,86,87,93,95] contend that it is necessary to provide additional training to improve knowledge of ASD and to overcome misconceptions and lack of information. It is important to consider this pressing need for training not only for pre-service teachers in teacher training colleges [39][40][41]96], but also lifelong learning for in-service teachers of mainstream schools, universities and other educational placements [25].…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, teachers must be educated in order to help students with ASD [26]. Regarding the university stage, the number of university students with autism is increasing, and it is crucial that these students can access adequate support [55,56]. However, a survey revealed that campus members, including faculty professors, had limited knowledge about ASD [57].…”
Section: Teachers' Knowledge Of Asd and Stagesmentioning
confidence: 99%
“…In this sense, education is a key area for the promotion and acquisition of competencies, knowledge, attitudes, social skills, healthy lifestyles, and participatory norms linked to sustainable development [28]. It is the perfect ground for current generations to internalize the importance of developing without compromising the possibility that future generations will be able to do so as well [29][30][31]. We must therefore generate spaces for debate and reflection where people can analyze, understand, internalize, and put into practice actions in favor of sustainable development, with the educational context being the ideal framework for working on 2030 Agenda.…”
Section: Agenda and Quality Educationmentioning
confidence: 99%
“…Caird et al 9 calculated that among 15 higher education institutions in the UK, distance-based education models achieved an 83% reduction in carbon emissions, with the fully online model achieving the lowest carbon emissions. Similarly, Perales Jarillo et al 10 have set the benefits of online education in the context of Sustainability Development Goals.…”
Section: Discussionmentioning
confidence: 99%